Rebuttal for thesis: antiplasmodial potential of South African medicinal plants and phytochemical investigation of Aloe marlothii, Turraea obtusifolia and Artemisia afra for identification of their active compounds. - Maharaj, Vinesh J. (University of Pretoria, 2023)
Rebuttal Thesis (Chemistry)--University of Pretoria, 2023.